EVALUASI KONEKTOR YANG ERGONOMI DALAM PERANCANGAN DESAIN GUNA PEMBERIAN EVALUASI DESAIN PRODUK TEMPAT DUDUK - Hessa Sinai Singadipoera; Kurniansyah Kurniansyah; Lutfy Eka Biardian (Sekolah Tinggi Teknologi Industri Padang, 2022)
Background the conducted in order to produce a design that is in accordance with the design design, it takes stages of activities such as planning or development. This starts from the idea search stage, problem analysis and followed by the development stage, in the form of concepts, systems and details. In addition, it can also be made protected, production activities, evaluation or product trials, then end in the distribution section. Purpose in this research to provide appropriate design results and also pay attention in terms of human factors and their activities. Like the size, body shape, position position, behavior and also habits during activities. Research in result will the achievement of good and correct work productivity. In paying attention to this, ergonomic consideration is needed. Ergonomics is part of the requirements for achieving qualified, certified design and customer needs. In addition, how far the design has met the functional technical factors, the quality of aesthetic and also economical. So in this case an evaluation is needed that can use the benchmark. Ergonomics are needed to evaluate the product. In addition to the conclusions, in terms of functional, the design must also be able to provide the impression of safety, health and comfort for users (humans) when it is published or operated by the product from the product.